Human B Cell-Derived Lymphoblastoid Cell Lines Constitutively Produce Fas Ligand and Secrete MHCII+FasL+ Killer Exosomes - Klinker, Matthew W.; Lizzio, Vincent; Reed, Tamra J.; Fox, David A.; Lundy, Steven K. (Frontiers in Immunology, 2014)
Immune suppression mediated by exosomes is an emerging concept with potentially immense utility for immunotherapy in a variety of inflammatory contexts, including allogeneic transplantation. Exosomes containing the apoptosis-inducing molecule Fas ligand (FasL) have demonstrated efficacy in inhibiting antigen-specific immune responses upon adoptive transfer in animal models. We report here that a very high frequency of human B cell-derived lymphoblastoid cell lines (LCLs) constitutively produce MHCII+FasL+ exosomes that can induce apoptosis in CD4+ T cells. All LCLs tested for this study (>20 independent cell lines) showed robust expression of FasL, but had no detectable FasL on the cell surface. Given this intracellular sequestration, we hypothesized that FasL in LCLs was retained in the secretory lysosome and secreted via exosomes. Indeed, we found both MHCII and FasL proteins present in LCL-derived exosomes, and using a bead-based exosome capture assay demonstrated the presence of MHCII+FasL+ exosomes among those secreted by LCLs. Using two independent experimental approaches, we demonstrated that LCL-derived exosomes were capable of inducing antigen-specific apoptosis in autologous CD4+ T cells. These results suggest that LCL-derived exosomes may present a realistic source of immunosuppressive exosomes that could reduce or eliminate T cell-mediated responses against donor-derived antigens in transplant recipients.